Exposure and behavioural response of satellite-tracked Cuvier’s beaked whales (Ziphius cavirostris) to naval traffic in the western Mediterranean Sea - BORRONI, ANNA (Università degli studi di Genova, 2024)
Cuvier’s beaked whale (Ziphius cavirostris G. Cuvier, 1823) is the only Ziphiidae species commonly found in the Mediterranean Sea. The Mediterranean population has been listed as ‘Vulnerable’ in the IUCN Red Data List as a result of the limited number of mature individuals (< 10,000) and the high genetic differentiation and isolation from the neighbouring Eastern North Atlantic. Moreover, recent genetic assessments found that Cuvier’s beaked whales inhabiting the Mediterranean Sea are clustered in two different evolutionarily significant units (ESUs) belonging to each distinct basin, the western and the eastern basins. Such ESUs have low genetic diversity and historical demography indicative of population contraction. One of the Cuvier’s beaked whale’s high-density areas in the Mediterranean Sea is the Ligurian Sea, where the ‘International Sanctuary for Protection of Mediterranean Marine Mammals’, the Pelagos Sanctuary, is located. Facing the Sanctuary are densely inhabited coastlines, with economically important urban, industrial, touristic, and agricultural activities. As a consequence, the maritime traffic in its waters is particularly intense with noise levels that are sufficient to cause behavioural disturbance to cetaceans. The small population size, the high degree of site-fidelity, and the genetic structure of the Mediterranean Cuvier’s beaked whales may render them particularly vulnerable to such intense shipping disturbance. In this study, we estimated the exposure of Cuvier’s beaked whale in the Ligurian Sea to shipping disturbance and the potential changes in its diving behaviour and movement pattern. First, we started by analysing the horizontal and vertical movement separately, using the first location and diving profile data collected from satellite-linked depth-recording tags deployed on eight animals in this area. The locations nonuniformly collected over deployment time, were fit by a Continuous-Time Correlated Random Walk model (CTCRWs) to simulate 100 1-hour resolution tracks for each ...